MATHEMATICS TOOLS DEVELOPMENT BASED ON WEB WITH MOODLE APPLICATIONS IN BASED STATISTICS SUBJECT - s, febrian dewanto, bagus ardi s, rina dwi (Phenomenon : Jurnal Pendidikan MIPA, 2014)
This research is the development of learning tools, which aims to: (1) describe the development of tools and produce mathematics learning application based on WEB with MOODLE Application On valid Based Statistics Subject. (2) To determine Effectiveley results the tools of learning. Moreover, the learning tools to be developed are the whole Syllabus, lesson plans, and text book learning. Those tools are developed by using the development model of 4D thiagdarajan Field trials conducted an web learning course on Education Statistics experiments Class, in this study were 36 students at class 3A, while the control class is 35 students of 3B class. Independent variables are motivation and activity, while the dependent variable is the learning achievement. Data taken with the deployment of questionnaires, observation and tests. Data processed with comparisons t test and regression.The results the influence of motivation and activity of learning achievement of 89.7% d) and the average ofÂ  learning achievement experimental class achieve exhaustiveness 74.25 e) Average learning achievement ofÂ  experimental class 74.25, better than average learning achievement for control class 64.57. Based on the research results obtained are valid learning tools and effective learning that show the development of learning tools goals achieved.